1990
DOI: 10.1007/bf01186082
|View full text |Cite
|
Sign up to set email alerts
|

Screening of rice (Oryza sativa L.) genotypes for physiological characters contributing to salinity resistance, and their relationship to overall performance

Abstract: Phenotypic resistance of salinity is expressed as the ability to survive and grow in a salinised medium. Some subjective measure of overall performance has normally been used in plant breeding programmes aimed at increasing salinity resistance, not only to evaluate progeny, but to select parents. Salinity resistance has, at least implicitly, been treated as a single trait. Physiological studies of rice suggest that a range of characteristics (such as low shoot sodium concentration, compartmentation of salt in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

18
218
1
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 352 publications
(244 citation statements)
references
References 16 publications
18
218
1
1
Order By: Relevance
“…In support of this idea, Jha et al (2010) have shown that there is a positive relationship between salt tolerance and expression levels of AtAVP1, which encodes an H + -pumping pyrophosphatase that is likely to be critical in the vacuolar sequestration of Na + . In contrast to such studies, however, the survey of rice cultivars by Yeo et al (1990;see above) indicated that there was no correlation between shoot Na + and tissue tolerance; moreover, tissue tolerance was negatively correlated with both plant survival and plant vigour. In any case, even when increased shoot Na + and increased salt tolerance occur together, the term "tissue tolerance" appears somewhat weak.…”
Section: Sodium Toxicitymentioning
confidence: 73%
See 2 more Smart Citations
“…In support of this idea, Jha et al (2010) have shown that there is a positive relationship between salt tolerance and expression levels of AtAVP1, which encodes an H + -pumping pyrophosphatase that is likely to be critical in the vacuolar sequestration of Na + . In contrast to such studies, however, the survey of rice cultivars by Yeo et al (1990;see above) indicated that there was no correlation between shoot Na + and tissue tolerance; moreover, tissue tolerance was negatively correlated with both plant survival and plant vigour. In any case, even when increased shoot Na + and increased salt tolerance occur together, the term "tissue tolerance" appears somewhat weak.…”
Section: Sodium Toxicitymentioning
confidence: 73%
“…Until these accumulation issues are better resolved, the roles of Na + transporters in salt tolerance and toxicity will not be adequately understood. What is clear at this point is that salinity stress and tolerance is a complex, multi-faceted trait, and cannot be predicted by simple indicators such as Na + accumulation (Yeo et al 1990;Møller and Tester 2007;Rajendran et al 2009). …”
Section: Sodium Toxicitymentioning
confidence: 99%
See 1 more Smart Citation
“…There is an overwhelming eotisensus in the literatute that exeessive concentration of salts in the cytoplastn is damaging to the functioning of eukaryotic cells (see e,g, reviews by Flowers et al 1977Flowers et al , 1986Greenway & Munns 1980;Munns & Tertnaat 1986), It is therefore difficult to see how sodium aeeumulalion, at least in excess of that which could be used for osmotic adjusttnent, can be of advantage to a higher plant, Sodiutn uptake in riee is exeessive by this definition and within a genotype is associated with (Yeo et al 1991), However, sodiutn uptake aecounted for only a stnall proportion of the vat iance in survival, as a tneasure of overall perfortnanee, when a large number of genotypes of rice were investigated (Yeo et al 1990), The reasons for this are exatnined in detail by Yeo et al (1990), Yeo (1994) and Flowers & Yeo (1995) and ean be sutntnarized as follows. Salt toleranee in riee is a eotnplex eharaeter eomprising a nutnber of cotnpotient traits (whieh inelude sodiutn uptake and eotnparttnetitalizatioti).…”
Section: Introductionmentioning
confidence: 99%
“…To improve the growth and yield, we need to develop plants with tolerance to salinity in the soil. Evaluating tolerance to saline conditions in plants requires evaluation of a complex set of physiological traits measured by components such as: plant survival scores, plant vigor, green leaf area, ion concentration and osmosis (Yeo et al, 1990;Sabouri and Sabouri, 2008). The main mechanisms of salt tolerance in crops include: ion homeostasis, osmotic homeostasis, and control and repair of oxidative stress damage (Verslues et al, 2006).…”
mentioning
confidence: 99%